Facile synthesis of nanoporous Mg crystalline structure by organic solvent-based reduction for solid-state hydrogen storage - Hyesun Kim; HyeonJi Kim; Wonsik Kim; Choah Kwon; Si-Won Jin; Taejun Ha; Jae-Hyeok Shim; Soohyung Park; Aqil Jamal; Sangtae Kim; Eun Seon Cho (Nature Communications)
Abstract Nanoporous metals have unique potentials for energy applications with a high surface area despite the percolating structure. Yet, a highly corrosive environment is required for the synthesis of porous metals with conventional dealloying methods, limiting the large-scale fabrication of porous structures for reactive metals. In this study, we synthesize a highly reactive Mg nanoporous system through a facile organic solution-based approach without any harsh etching. The synthesized nanoporous Mg also demonstrates enhanced hydrogen sorption kinetics and reveals unique kinetic features compared to Mg nanoparticles. The well-crystallized Mg nanoporous structure exhibits crystalline facet-dependent hydrogen sorption characteristics, featuring gradually improved hydrogen storage capacity up to 6 wt.% upon cycling. Also, continuum kinetics models coupled to atomistic simulations reveal that the compressive stress developed during the hydrogenation of nanoporous Mg enhances the sorption kinetics, as opposed to the sluggish kinetics under tensile stress in core-shell nanoparticles. It is expected that the synthetic strategy conceived in this study can be further implemented to prepare different kinds of reactive porous metals in a facile and scalable way for the development of large-scale and distributed hydrogen storage systems for the emerging low-carbon hydrogen economy.